2001
DOI: 10.1097/00001813-200111000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Increased cytotoxicity and stability of Lipiodol-pirarubicin emulsion compared to classical doxorubicin-Lipiodol: potential advantage for chemoembolization of unresectable hepatocellular carcinoma

Abstract: 경우 Grade 0, 리피오돌 결절성반점이 1-3개있는 경우 Grade 1, 결절성반점 이 4개이상 또 는 반월성반점이 한 개있는 경우 Grade 2, 그리고 반월성반점이 둘이상 있는 경우 Grade 3 으로 분류하였다. CT 촬영후 신장을 적출하여 조직표본을 만들고 CT 영상소견과 비교하였 다. 조직절편에 나타난 병변의 크기 측정은 신우를 중심으로 횡절단한 슬라이 스를 1: 1 로 인화지 촬영한후 방안지를이용하여 측량한후백분율을내었다. 결 과 : 현미경학적으로 이상이 있는 조직의 육안적 이상 소견은 염증세포 침윤과 리피 오돌 소적 이 있는 부위는 미세한 까만점의 무리로, 이영양성 석회화가 있는 부위는 암갈색 반점의 무리로,그리고세포괴사가있는부위는균절한펑크색 바탕으로나타났다. Grade 0 인 5예의 조직학적 병변의 크기는 평균 2.2%, Grade 1 인 4예는 평균 4.5 %, Gr ade 2 인 7예 는 평균 21.9%, 그리고 Grade 3 인 4예는 평균 24%로 CT 영상에서 결절성 반점 (nodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…On the contrary, the phase separation for lipiodolidarubicin emulsion was very limited (5 % aqueous solution and 95 % persisting emulsion); fluorescent electronic microscopy revealed that idarubicin was inside and at the periphery of lipid droplets as a result of drug-lipid ionic interactions. This enhanced emulsion stability is probably an advantage in increasing the contact time of the drug with cancer cells, as previously reported [30].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…On the contrary, the phase separation for lipiodolidarubicin emulsion was very limited (5 % aqueous solution and 95 % persisting emulsion); fluorescent electronic microscopy revealed that idarubicin was inside and at the periphery of lipid droplets as a result of drug-lipid ionic interactions. This enhanced emulsion stability is probably an advantage in increasing the contact time of the drug with cancer cells, as previously reported [30].…”
Section: Discussionsupporting
confidence: 75%
“…We took advantage of the higher lipophilicity of idarubicin, resulting in a great accumulation of the drug in the oily phase, thereby permitting lipiodol to act as a slow-releasing vector. Favoulet et al [30] demonstrated that lipiodol-doxorubicin emulsion was completely separated into two phases (oil and aqueous) after only 20 min. This might explain the pharmacokinetic data demonstrating that the intra-arterial administration of doxorubicin emulsified with lipiodol has little effect compared with intravenous administration of doxorubicin alone [31].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Anticancer drug delivery by hepatic arterial chemoembolization using GSP and/or IOE has been widely used in clinical settings to treat HCC efficiently, without significantly changing hepatic function due to the liver's duplex blood supply systems. 7,8 Although it is not via blood vessel, an efficient and localized transgene expression has been successfully achieved using gelatin sponge sheets (GSS) in a rat Achilles tendon (for 17 days) and mouse cochlea. 11,12 Taken these findings together, we hypothesized that catheter-mediated hepatic arterial embolization with GSP would enhance transgene expression efficiency into hepatocytes, because of the low clearance rate and long contact time of adenovirus soaked in GSP.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 Transcatheter hepatic arterial chemoembolization using emulsions of anticancer agents, iodized oil esters (IOE) and/or GSP has been determined to be an efficient and safe palliative treatment for inoperable hepatocellular carcinoma (HCC), offering prolonged survival and good life quality. 7,8 As GSP induces embolization and is absorbed slowly, without inducing excessive inflammatory reaction or irritation, 8 anticancer agents soaked in GSP are released slowly into the liver environment. We asked whether adenoviral vectors, rather than anticancer drugs soaked in emulsion of GSP, might be released slowly after catheter-mediated embolization, a process that we hoped might increase transduction efficiency and/ or decrease viral clearance.…”
mentioning
confidence: 99%
“…After embolization of APS, the routine interventional therapy was done for the tumor, as reported [11][12][13][14][15] . After catheter was inserted into feeding artery of tumour, pirarubicin (THP)/lipiodol(LPD) emulsion was injected through catheter for the patients without tumour thrombus in main portal vein.…”
Section: Treatmentsmentioning
confidence: 99%